2005
DOI: 10.1038/nbt1113
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput generation of small antibacterial peptides with improved activity

Abstract: Cationic antimicrobial peptides are able to kill a broad variety of Gram-negative and Gram positive bacteria and thus are good candidates for a new generation of antibiotics to treat multidrug-resistant bacteria. Here we describe a high-throughput method to screen large numbers of peptides for improved antimicrobial activity. The method relies on peptide synthesis on a cellulose support and a Pseudomonas aeruginosa strain that constitutively expresses bacterial luciferase. A complete substitution library of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
319
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 361 publications
(329 citation statements)
references
References 13 publications
5
319
2
3
Order By: Relevance
“…Sample Sources and Preparation. Sub6 (RWWKI-WVIRWWR-NH 2 ), 27 an optimized variant of Bac2A, which in turn is a linearized version of bactenecin, a naturally occurring bovine peptide, 28 was synthesized by P. Henklein using 9-fluorenylmethyl carbamate (fMOC) solid-phase synthesis. Indolicidin (ILPWKWPWWPWRR-NH 2 ) was synthesized by P. Owen at the Peptide Synthesis Facility, Biomedical Research Centre, UBC, using tertiary butyloxycarbonyl (tBOC) solidphase synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Sample Sources and Preparation. Sub6 (RWWKI-WVIRWWR-NH 2 ), 27 an optimized variant of Bac2A, which in turn is a linearized version of bactenecin, a naturally occurring bovine peptide, 28 was synthesized by P. Henklein using 9-fluorenylmethyl carbamate (fMOC) solid-phase synthesis. Indolicidin (ILPWKWPWWPWRR-NH 2 ) was synthesized by P. Owen at the Peptide Synthesis Facility, Biomedical Research Centre, UBC, using tertiary butyloxycarbonyl (tBOC) solidphase synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Since purity and quantity of the peptides synthesized on cellulose may vary, all results achieved using this method need to be confirmed with peptides produced by conventional solid-phase peptide synthesis on resin. It is worth noting that antibacterial activity assays with soluble peptides usually confirm the activity of peptides synthesized on cellulose 8,10 . However, the correct design and preparation of the assay are critical to the success of the method.…”
Section: Experimental Designmentioning
confidence: 93%
“…Screening large numbers of peptides using peptide synthesis on resin is labor intense and expensive. At only approximately 1% of the cost per peptide compared to the conventional peptide synthesis on resin, the synthesis of arrays of peptides on cellulose using SPOT technology represents a powerful tool for characterizing or screening large numbers of peptides for antimicrobial activity [6][7][8][9] . Using SPOT synthesis, up to 1,000 peptides per 20 Â 29-cm 2 cellulose sheet can be synthesized in a highly parallel and addressable manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many synthetic variants of cationic antimicrobial peptides have been generated by Hancock and co-workers, who have observed that Arg and Trp predominate in high activity peptide sequences [56][57][58], including that of clinical candidate MX226 (Omiganan) [57]. Other short synthetic peptides containing Arg-Trp have also been reported to show high levels of antimicrobial activity [59,60], even dipeptide derivatives based upon Trp-Arg [61].…”
Section: A Novel Site Of Action For Cationic Antimicrobial Peptides Cmentioning
confidence: 99%